Migración haitiana de tránsito: la ruta migratoria por Santiago de Chile y la aspiración de llegar hacia el norte global - Lissette Madriaga-Parra; Nicolás Gissi-Barbieri (Antípoda: Revista de Antropología y Arqueología)
This article examines Haitian migration to Santiago, Chile, with a particular focus on the primary transit routes taken by this group and the challenges they face upon arrival. Many Haitians subsequently re-emigrate with new migration plans aimed at reaching the Global North. The study adopts a qualitative methodology, including fieldwork conducted from 2015 to 2023 in communes within Greater Santiago. It incorporates in-depth interviews with Haitian residents in these areas, alongside an analysis of national and international digital media and other documentary sources. The findings reveal two main migration routes: an aerial route leading to Santiago, Chile, and Quito, Ecuador, and an overland route from Quito to the northern Peru-Chile border, culminating in Santiago. Initially, many Haitians viewed life in Chile as a “salvation” from socioeconomic challenges. However, this perception often deteriorates over time due to widespread discrimination, which redirects their migration journey. Anti-Haitian policies, marked by both institutional and everyday racism, leave this group grappling with precarious, low-wage jobs and substandard housing in stigmatized areas. In these environments, evangelical churches have emerged as critical spaces, providing both symbolic meaning and opportunities for building and strengthening migration networks. An important finding is that, from the outset, many Haitians perceive Chile as a transit country, using it as a stepping stone for overland migration to the northern border of Mexico and the United States. Despite their aspirations for better job opportunities, they increasingly face similar challenges, such as precarious living conditions, difficulties in regularizing immigration status, and systemic racism, mirroring those in the Global South.